Investigating Minimum Quantity Lubrication in Unidirectional Cf/SiC composite grinding. Issue 3 (15th February 2020) - Qu, Shuoshuo; Gong, Yadong; Yang, Yuying; Sun, Yao; Wen, Xuelong; Qi, Yang
Abstract: The influences of minimum quantity lubrication (MQL) on the grinding performance of unidirectional carbon fibre-reinforced ceramic matrix (Cf /SiC) composites were investigated in this paper. The experimental results indicate that MQL can significantly improve surface quality and reduce grinding forces. In addition, MQL has a low cost and does not generate considerable pollution. According to the lubrication mechanism of MQL, the effects of nozzle direction, air pressure, oil flow rate and nozzle distance on the grinding performance of unidirectional Cf /SiC composites were carefully investigated in this research. Excellent surface quality and low grinding forces can be achieved when the nozzle direction, air pressure, oil flow rate and nozzle distance are 15°, 5 bar, 100 ml/h and 80 mm, respectively. The surface topographies show that smooth fibre separation, fibre breaking, fibre outcropping, fibre pullout and matrix cracks are the main failure forms of the ground surface. The histogram reflects that the proportion of fibre pullout is the highest, whereas that of fibre outcropping is lowest. In the MQL grinding process, a large amount of heat is removed by water vapour, which can significantly reduce the grinding temperature. Meanwhile, effective oil films form in the contact areas between the grits and the material surface. The above factors are advantageous for improving the grinding performance of unidirectional Cf /SiC composites. The objective of this research was to investigate the influences of MQL for unidirectional Cf /SiC composites, validate these interpretations with experimental results and provide reasonable recommendations for guaranteeing the machining accuracy of Cf /SiC composites.